Symbolic estates: community identity and empowerment through heritage - Stephens, John; Tiwari, Reena (Taylor Francis, 2015)
Heritage is important for the social and cultural health of communities, whilst local stewardship of cultural heritage has the capacity to empower and recover cultural identity. This paper describes a recent project in Lakhnu – a small rural village in Uttar Pradesh, India – to restore a nineteenth century villa formerly used as the village school as an educational facility. In this discussion, we draw attention to the right of groups to manage their culture. The loss of cultural heritage is linked to a loss of identity. We argue that heritage projects have the capacity to empower communities to sustain their heritage and identity and provide useful places for social and material advancement through the concept of a shared ‘symbolic estate’. At Lakhnu, we plan to evoke grass-root conservation where local communities become the rightful stakeholders and decision-makers who are encouraged and facilitated in the realisation of their right to cultural heritage and to stimulate growth and build capacity for the community.